EFFICIENCY APPLICATION OF BACTERIA LYSATES WITHIN PREVENTIVE ACTIONS AMONG CHILDREN - S.P. Kokoreva; N.P. Kuprina; V.N. Ragozina; N.I. Pokataeva; E.V. Aralova ("Paediatrician" Publishers LLC, 2007)
The authors demonstrate the research findings of the preventive efficiency showed by the bacteria lysates mixture (imudon) among preschool children (n = 23), visiting organized collectives. They prove that the medication has good tolerance and marked efficiency, as well as contributes to the reduction of the acute respiratory infections, their much easier run, rehabilitation of the disturbed fauces microbiocenosis, normalization of the immunoglobulin profile within the system of the local and general immunity. Key words: children, bacteria lysates mixture, acute respiratory infections, prevention.